Achieving Academic Success Through Fostering Career Planning of Nepalese Higher Secondary Students - Neupane, Krishna Prasad; Dhakal, Hem Chandra; Budhathoki, Dhruba Kumar; Chalise, Dhan Raj (International Journal of Silkroad Institute of Research and Training, 2023)
Background: High school students often view career planning as a task for college, but initiating this process during high school is crucial for continuous self-discovery. This approach aims to enable citizens to navigate the complexities of the ever-changing labor market effectively. Method: Descriptive and exploratory research methodologies, strategically chosen to identify problems and illuminate current marketing conditions and practices within the realm of higher secondary schools. The target population encompasses all higher secondary schools and their students in Kathmandu Valley, with a sample of 25 colleges selected using a convenience sampling method. Result: The findings of the study exhibited noteworthy consistencies in responses across different demographic groups, thus providing a basis for generalization among the target audience. The study highlighted that a career is a composite outcome of job-related experiences acquired throughout an individual's professional journey. Furthermore, the research underscored the dynamic nature of career planning, which continuously adapts to the rapid changes in the global economy. The evolving landscape of career planning places a strong emphasis on career building, with the overarching goal of assisting individuals in developing resilience and self-reliance. Conclusion: This study emphasized the importance of maintaining a harmonious balance between work and life roles, recognizing the significance of holistic career development in the contemporary socio-economic context.